2012
DOI: 10.1126/science.1215909
|View full text |Cite
|
Sign up to set email alerts
|

ER Cargo Properties Specify a Requirement for COPII Coat Rigidity Mediated by Sec13p

Abstract: Eukaryotic secretory proteins exit the endoplasmic reticulum via transport vesicles generated by the essential COPII coat proteins. The outer coat complex, Sec13-Sec31, forms a scaffold that is thought to enforce curvature. By exploiting yeast bypass-of-sec-thirteen (bst) mutants, where Sec13p is dispensable, we probed the relationship between a compromised COPII coat and the cellular context in which it could still function. Genetic and biochemical analyses suggested that Sec13p was required to generate vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
132
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 42 publications
9
132
0
Order By: Relevance
“…When SEC13 is mutated, the COPII coat may become too flexible and unable to form transport vesicles containing asymmetrically distributed cargoes such as GPI-anchored proteins that confer opposing curvature. Since mutations in genes encoding proteins involved in GPI remodeling and cargo receptors prevent from concentrating GPI-anchored proteins at ER-exit sites, transport vesicles could be formed even in the absence of SEC13 (81,82). These results also suggest that structural remodeling of GPIanchors is required for the sorting of GPI-anchored proteins into the ER-exit sites.…”
Section: Er-to-golgi Transport Of Gpi-anchored Proteinssupporting
confidence: 55%
See 1 more Smart Citation
“…When SEC13 is mutated, the COPII coat may become too flexible and unable to form transport vesicles containing asymmetrically distributed cargoes such as GPI-anchored proteins that confer opposing curvature. Since mutations in genes encoding proteins involved in GPI remodeling and cargo receptors prevent from concentrating GPI-anchored proteins at ER-exit sites, transport vesicles could be formed even in the absence of SEC13 (81,82). These results also suggest that structural remodeling of GPIanchors is required for the sorting of GPI-anchored proteins into the ER-exit sites.…”
Section: Er-to-golgi Transport Of Gpi-anchored Proteinssupporting
confidence: 55%
“…These mutations are called "bypass-of-sec-thirteen (BST)" mutations. Recently, it was reported that other GPI remodeling genes or other p24 family members, including PER1, TED1, GUP1, ERP1 and ERP2, function as BST genes, and that mutations in these genes suppressed the lethality of sec13∆ cells (81). The relationship between SEC13 and BST genes can be explained as follows.…”
Section: Er-to-golgi Transport Of Gpi-anchored Proteinsmentioning
confidence: 99%
“…Thus, although Sar1 and Sec23/Sec24 may participate in membrane curvature, the majority of membrane bending force likely comes from Sec13/Sec31. Indeed, recent genetic and biochemical experiments support this model: Sec31 likely forms all the contacts needed to make the COPII cage (Fath et al 2007) with Sec13 providing structural rigidity to the cage edge element to overcome the membrane bending energy of a cargo-rich membrane (Copic et al 2012). The fundamental function of vesicles is to ensure directional traffic of protein cargoes, making cargo capture an integral part of coat action.…”
Section: Transport From the Er: Sculpting And Populating A Copii Vesiclementioning
confidence: 93%
“…Thus, CLCs may contribute to uptake of cargoes that pose particular membranebending challenges. Analogously, Sec13p in COPII-coated vesicles contributes structural rigidity that is required to bend membranes with asymmetric cargo, such as GPI-anchored receptors (36). Two GPCR cargoes (μ-opioid receptor and CXCR4) that require CLCs for endocytosis are modified by ubiquitin, which attracts specific endocytic adaptors to promote uptake by clathrin-coated pits (5,31,37).…”
Section: Clc Depletion From Cell Lines Establishes Selectivity For DImentioning
confidence: 99%